Increased Ice Thinning over Svalbard Measured by ICESat/ICESat-2 Laser Altimetry - Lukas Sochor; Thorsten Seehaus; Matthias H. Braun (Remote Sensing, 2021)
A decade-long pronounced increase in temperatures in the Arctic, especially in the Barents Sea region, resulted in a global warming hotspot over Svalbard. Associated changes in the cryosphere are the consequence and lead to a demand for monitoring of the glacier changes. This study uses spaceborne laser altimetry data from the ICESat and ICESat-2 missions to obtain ice elevation and mass change rates between 2003–2008 and 2019. Elevation changes are derived at orbit crossover locations throughout the study area, and regional volume and mass changes are estimated using a hypsometric approach. A Svalbard-wide annual elevation change rate of −0.30 ± 0.15 m yr−1 was found, which corresponds to a mass loss rate of −12.40 ± 4.28 Gt yr−1. Compared to the ICESat period (2003–2009), thinning has increased over most regions, including the highest negative rates along the west coast and areas bordering the Barents Sea. The overall negative regime is expected to be linked to Arctic warming in the last decades and associated changes in glacier climatic mass balance. Further, observed increased thinning rates and pronounced changes at the eastern side of Svalbard since the ICESat period are found to correlate with atmospheric and oceanic warming in the respective regions.